UPAYA PERLINDUNGAN HUKUM TERHADAP KONSUMEN ONLINE DI INDONESIA - Darmayanti, Ni Kadek; -, Yuwono (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
This paper titled legal safeguards against online shopping consumers in Indonesia, in the her writing using normative legal research methods, namely by way of reading, studying, and analyzing various laws,literature, scientific papers, and papers relating to material The meticulous. Online shopping is a way of shopping via the internet virtual world where the payer uses a credit card or debit card, so no need to meet face to face. Or in this case the buyer is a consumer can order the goods to the seller throughout Indonesia so easily. Therefore in this paper will explain in general on legal protections for online consumers shopping in Indonesia.
Keywords: Online Shopping, Konsumen